Efficacy of propolis extract against Colletotrichum sp. causing anthracnose diseases of mango fruit cv. Aok Rong - Nuchnuanrat, Phikun; Jitsatta, Napaporn (RMUTSB ACADEMIC JOURNAL, 2023)
The efficacy of stingless bee propolis extract obtained from Laem Sing, Makham, and Tha Mai district in Chanthaburi province, was studied to inhibit the growth of Colletotrichum sp. causing anthracnose disease of mango cv. Aok Rong on the culture medium. The study showed that the propolis extract at concentrations of 1, 2, 3% (w/v) compared to prochloraz 0.05% (v/v) significantly (p<0.01) inhibited the mycelium growth and spore germination of the tested fungi. The effective treatments were propolis from Laem Sing District at 3%, propolis from Tha Mai district at 2%, and prochloraz at 0.05%, showing 100.00% inhibition of mycelium growth and spore germination of Colletotrichum gloeosporioides, followed by propolis from Makham at 3 and 2% inhibited mycelium growth by 87.11 and 71.24% while inhibiting the spore germination by 93.96 and 84.66%, respectively. In conclusion, propolis extract obtained from three districts in Chanthaburi province shows antifungal activities to inhibit the growth of Colletotrichum sp. causing anthracnose disease in mango. The chemical composition and antifungal properties of propolis extracts should be included in future studies.